(untitled) (CIPEEX, 2025)
Odontomas are mixed odontogenic tumors composed of both epithelial and ectomesenchymal tissues, with structural anomalies that classify them as hamartomas rather than true neoplasms. This report aims to describe the surgical removal of a complex odontoma located in the left mandibular body of a 12-year-old patient. The patient presented with a painless swelling in the left mandibular region and failure of eruption of the lower left premolars. The panoramic X-ray revealed an amorphous radiopaque image with impaction of the lower premolars. Cone beam computed tomography showed a large, amorphous, hypodense mass measuring 23.39 mm at its largest dimension, surrounded by thin cortical bone, which posed a high risk of mandibular fracture after enucleation. Complete enucleation of the lesion was performed conservatively, without the need for fixation plates or screws. The patient received postoperative care instructions for four months. At the five-month follow-up, the patient showed complete healing and satisfactory bone regeneration, with no complications or signs of recurrence.